THE RESEARCH OF CORNER LAYING GRAINS OF THE GRANULAR MATERIAL ON THE CAPACITY MODEL - Bannikov, D. O. (Science and Transport Progress, 2008)
In the paper the results of the author’s experimental observations with a transparent model of reservoir of vertical cross-section are presented. The observations were devoted to the character of packing the grains of loose material. The influence of a side-wall angle of the reservoir and rate of its filling on a packing angle of the loose material is shown. The processes of filling and empting the model reservoir are analyzed. The effect of changing the direction of friction forces between the grains of the loose material in the beginning of empting was discovered.